The Fall of the Republic Government in Afghanistan and the Current Taliban Rule: A Survey of Public Attitudes - Ahmadi, Ramazan; HİKMAT, Chman Ali (Research in Social Sciences and Technology, 2023)
This paper represents one of the most recent and pertinent studies conducted in Afghanistan, aiming to address the societal imperative of comprehending the factors behind the fall of the Republic government and the subsequent rise of the Taliban to power. Furthermore, the paper seeks to analyse public attitudes towards the current situation. Employing a quantitative approach, the research utilizes a descriptive-analytical method through questionnaires and the participants include social media activist, students and universities professors, the data collected by online survey according WhatsApp, Facebook messengers, telegram, email and other social media groups from different ethnic groups. The findings of this research have identified several pivotal factors contributing to the ascent of the Taliban to power, including the US-Taliban agreement in Doha, Qatar; political disparities; administrative and financial corruption within the Republic's administration; Pakistan's support for the Taliban; the previous government's accord with the Taliban; ethnic dominance; robust military morale of the Taliban; and proficient war management by the Taliban. Afghanistan, as a multi-ethnic society, witnesses political dynamics predominantly rooted in ethnic affiliations. The majority of respondents express dissatisfaction with the current Afghan situation, displaying significant concerns for the populace. Foremost concerns, in terms of prioritization, encompass poverty; closure of girls' schools; restrictions on women's education and employment; escalation of civil unrest; mono-ethnic rule; ethnic conflicts; emergence of ISIS; ethnic marginalization; violations of citizenship rights; political participation and legitimacy crises; and authoritarianism. Consequently, to address the political crisis and establish a viable system, the research concludes that while Pashtuns lean toward a centralized system, Hazaras, Tajiks, Uzbeks, and Turkmens evince greater interest in a decentralized structure.